Analyse textométrique du lexique des personnages dans French Town de Michel Ouellette : dire je et exprimer ses émotions - Johanne Melançon (Humanités Numériques)
This textometric analysis, performed with the TXM software, offers a re-reading of a Franco-Ontarian play where each character is characterized by the language register he uses. The analysis of the lexicon of Michel Ouellette’s play French Town (1994) highlights the peculiarities of the language of Cindy, both in the way she tries to express herself, in her vocabulary and in her way of expressing her emotions. Thus, the “calcul des spécificités” method reveals that the three lexical units with the greatest frequency relate to the character of Cindy and their analysis shows how she manages to express her emotions although she has great difficulties to say I.